Green strategies for molecularly imprinted polymer development - Viveiros, Raquel (2019)
The authors would like to thank financial support from Fundacao para a Ciencia e Tecnologia, Ministerio da Ciencia, Tecnologia e Ensino Superior (FCT/MCTES), Portugal, through principal investigator contract IF/00915/2014 (T.C.). This work was also supported by the Associate Laboratory Research Unit for Green Chemistry-Clean Technologies and Processes-LAQV-REQUIMTE, financed by national funds from FCT/MCTES (UID/QUI/50006/2013) co-financed by the ERDF under the PT2020 Partnership Agreement (POCI-01-0145-FEDER-007265).